Trade openness and economic growth in rental economies Empirical evidence from Libya (Economic studies journal, 2022)
The aim of this study was to estimate the relationship between trade openness and economic growth in the Libyan economy, with special focus on its rental structure. In order to achieve its objective the study utilized correlation analysis, AARDL model, UECM based non-Granger causality test and Toda-Yamamoto non-Granger causality test. Long run coefficients and causality tests’ results indicated a positive relationship between trade openness and economic growth. In addition, this relationship is positively affected by the natural resources abundance index. However, it was found to be negatively affected by the natural resources dependency factor.
Keywords: Trade openness; Economic growth; rental structure; Libyan economy; causality